2023
DOI: 10.1002/ldr.4802
|View full text |Cite
|
Sign up to set email alerts
|

Influence mechanisms of N addition on the concentration of soil dissolved organic matter in China

Abstract: Soil dissolved organic matter (DOM) plays a critical role in regulating the cycling of terrestrial biogeochemistry. However, the influence mechanisms of nitrogen (N) addition on soil DOM concentration are not well understood at the regional scale. We performed a meta‐analysis of 1004 paired observations from 115 literature to explore how N addition affected the soil DOM concentration, including dissolved organic carbon (DOC) and nitrogen (DON), in China. Overall, N addition markedly stimulated the soil DOC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
(83 reference statements)
1
1
0
Order By: Relevance
“…Soil DOM characteristics showed a strong dependence on environmental variables (Figures 8 and 9), wherein pH exhibited a significant effect on soil DOM characteristics. Some studies have reported that the increase in N availability played a more important role in soil DOM concentration than the reduction in the stimulus for inhibiting soil pH (Xu et al, 2023). In the present study, the pH value of each treatment decreased, and pH was positively correlated with E 2 /E 3 (Figures 8 and 9).…”
Section: Influence Of Nutrient Addition On the Composition And Chemic...supporting
confidence: 57%
“…Soil DOM characteristics showed a strong dependence on environmental variables (Figures 8 and 9), wherein pH exhibited a significant effect on soil DOM characteristics. Some studies have reported that the increase in N availability played a more important role in soil DOM concentration than the reduction in the stimulus for inhibiting soil pH (Xu et al, 2023). In the present study, the pH value of each treatment decreased, and pH was positively correlated with E 2 /E 3 (Figures 8 and 9).…”
Section: Influence Of Nutrient Addition On the Composition And Chemic...supporting
confidence: 57%
“…2 b), which indicated that the adsorption capacity and affinity of organic contaminants with higher hydrogen-bonding donor ability tend to be less suppressed by the competition of FA. At a given FA concentration of 50 mg TOC/L, a high concentration level of DOM in natural water and soil water [ [39] , [40] , [41] , [42] ], adsorption of these selected organic contaminants in a wide concentration range (the relative equilibrium concentrations C e / S w ranged from about 0.0001 to 0.75) on KAC were not significantly suppressed by FA ( Fig. 3 a–g).…”
Section: Resultsmentioning
confidence: 99%